Common variants in genes involved in islet amyloid polypeptide (IAPP) processing and the degradation pathway are associated with T2DM risk: A Chinese population study. (March 2022) - Xu, Jie; Jin, Li; Chen, Jie; Zhang, Rong; Zhang, Hong; Li, Yangyang; Peng, Danfeng; Gu, Yunjuan; Wheeler, Michael B.; Hu, Cheng
Abstract: Aim: To explore the genetic effects of SLC30A8, IAPP, PCSK1, PCSK2, CPE, PAM and IDE, key genes involved in IAPP processing and degradation pathway on T2DM risk and metabolic traits in Chinese population. Methods: Common variants were genotyped in 10936 Chinese subjects by Asian Screening Array and Multi-Ethnic Global Array. Associations of SNPs with occurrences of T2DM and related traits were evaluated through logistic and multiple linear regression. Genetic risk score (GRS) model was constructed based on 6 T2DM-variants, and its relationship with T2DM and related traits was assessed. Results: SLC30A8 -rs13266634, PCSK1 -rs155980, PCSK2 -rs6136035, CPE -rs532192464, PAM -rs7716941, and IDE -rs117929184 were the top SNPs significantly associated with T2DM after adjusting for age, sex, and BMI, associated with blood glucose level, insulin secretion, and insulin sensitivity (all FDR p < 0.05). GRS calculated based on the above SNPs was remarkably correlated with T2DM, blood glucose, and insulin secretion. Furthermore, there was a significant interaction between SLC30A8 and IAPP in patients with T2DM (P = 0.0083). Conclusion: Our study showed that common variants in genes involved in IAPP processing and the degradation pathway were associated with T2DM in Chinese population. Subjects with high GRS exhibited poorer glucose metabolism and insulin secretion.